Advancing anesthesiology trainee proficiency in airway management via simulation-based training: a non-hypoxic apnea duration approach - Tang,Lijun; Zhang,Yi; Chen,Lianhua; Li,Jinbao; Huang,Shiwei; Fang,Bin; Huang,Xiaojing; Huang,Lina (PeerJ, 2025)
Background Effective airway management training for anesthesiology trainees remains crucial for patient safety. While simulation-based education has shown promise, incorporating physiological parameters into training scenarios could enhance learning outcomes. Objective To evaluate the impact of incorporating non-hypoxic apnea duration awareness in simulation-based airway management education for anesthesiology trainees. Methods This quasi-experimental study (ChiCTR2200065877) was conducted at Shanghai General Hospital from December 2022 to March 2023. Thirty anesthesiology undergraduates were randomly assigned to either an intervention group, which received non-hypoxic apnea duration information, or a conventional training group. Performance was assessed using a modified Direct Observation of Procedural Skills (DOPS) score and a satisfaction questionnaire. The intervention group was provided with specific non-hypoxic apnea duration data (247 s until SpO2 reached 90%) during simulated difficult airway scenarios. Results The intervention group demonstrated significantly higher modified DOPS scores (51.4 ± 4.4 vs. 43.0 ± 5.4, P < .001) and satisfaction scores (45.0 ± 1.4 vs. 43.1 ±  2.0, P = .005). Notable improvements were observed in pre-anesthesia preparation (P = 0.028), difficult airway management (P < 0.001), and crisis response (P < 0.001). These findings suggest that incorporating non-hypoxic apnea duration awareness enhances clinical skills and trainee satisfaction. Conclusions Incorporating non-hypoxic apnea duration awareness into simulation-based airway management training significantly enhances both clinical skills and trainee satisfaction. This approach shows promise for improving critical aspects of airway management education.
Keywords: Medical education; Simulation training; Airway management; Anesthesiology; Clinical competence; Educational measurement; Patient simulation